2009
DOI: 10.1111/j.1365-313x.2008.03758.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing by artificial microRNAs in Chlamydomonas

Abstract: SummaryChlamydomonas reinhardtii is a unicellular green alga. It is a model system for studying functions of the chloroplast, basal body and flagella. The completion of the Chlamydomonas genome sequence makes it possible to use reverse genetic approaches in this organism. Chlamydomonas contains a set of endogenous microRNAs (miRNAs) that down-regulate their target gene expression through mRNA cleavage. Here we developed an artificial miRNA-based strategy to knock down gene expression in Chlamydomonas. Using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
94
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 34 publications
(77 reference statements)
0
94
0
1
Order By: Relevance
“…Zhao et al have shown that the siRNA machinery functioning in Chlamydomonas, siRNA against MAA7 reduces the mRNA levels of MAA7 [4]. This leads to a reduction of the conversion of prodrug 5-FI to the highly toxic 5-FTryptophan.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhao et al have shown that the siRNA machinery functioning in Chlamydomonas, siRNA against MAA7 reduces the mRNA levels of MAA7 [4]. This leads to a reduction of the conversion of prodrug 5-FI to the highly toxic 5-FTryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the Nativis technology we targeted a well characterized enzyme in Chlamydomonas, the beta subunit of tryptophan synthase (MAA7) [4]. Zhao et al have shown that the siRNA machinery functioning in Chlamydomonas, siRNA against MAA7 reduces the mRNA levels of MAA7 [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA silencing technique has been successfully used to suppress endogenous transcript levels in Chlamydomonas [11][12][13] but it is difficult to obtain a complete loss-of-function RNA-silenced strain and there may be off-target effects induced by the introduced construct [6,10].…”
Section: Introductionmentioning
confidence: 99%